Inguinal herniation with hydrometra/mucometra in a poodle bitch - Sontas, B. Hasan (Canadian Veterinary Medical Association, 2013)
A 5-year-old, sexually intact poodle bitch was presented with a 2-year history of inguinal mass. A tentative diagnosis of hydrometra/mucometra with inguinal herniation was made and ovariohysterectomy with hernia repair was performed. Both fluid-filled uterine horns, both broad ligaments, and the uterine body were observed to be herniated through the inguinal ring. On histopathology, marked edema and diffuse hemorrhage were diagnosed in the uterus.